Philosophical Reflection and Cooperative Practices in an Elementary School Mathematics Classroom - Daniel, Marie-France; Lafortune, Louise; Pallascio, Richard; Schleifer, Michael (Canadian Journal of Education/Revue canadienne de l’éducation, 1999)
Following Matthew Lipman (Lipman, 1991; Lipman, Sharp, & Oscanyan, 1980), we introduced philosophical dialogue (PD) about mathematics in an elementary school to help pupils consider mathematical and meta-mathematical matters. This article describes the social and cognitive activity when pupils engage in PD and some pedagogical conditions necessary to foster the development of PD. Changes in pupils’ discussions from the begin- ning to the end of the test period showed that the dynamic evolved from monological exchanges to dialogical exchanges. Whereas early pupil responses could be characterized mainly as simple answers, later responses displayed more lower-order and even higher- order thinking skills. The data suggest that for PD about mathematics to develop, the teacher must be proficient in the role of mediator. À la suite de Matthew Lipman (Lipman, 1991; Lipman, Sharp et Oscanyan, 1980), les auteurs ont introduit le dialogue philosophique (DP) dans une école primaire afin d’aider les élèves à réfléchir aux questions d’ordre mathématique et méta-mathématique. Cet article décrit l’activité sociale et cognitive à laquelle donne lieu le DP ainsi que certaines des conditions pédagogiques qui doivent être réunies pour favoriser le développement du DP. L’analyse des discussions des élèves du début à la fin de la période d’essai a révélé une évolution de la dynamique, des échanges monologiques aux échanges dialogiques. Si en premier les élèves donnent de simples réponses, par la suite ils démontrent des capa- cités de raisonnement élémentaires et même de plus haut niveau. Ces données semblent indiquer que pour que le DP au sujet de la mathématique se développe, l’enseignant doit devenir un médiateur efficace.